Incidence and risk factors of retinopathy of prematurity - Rasyidah Rasyidah; Sujan Ali Fing (Indonesian Pediatric Society, 2013)
Background Retinopathy of prematurity (ROP) is one of themain causes of visual impairment in premature infants.Objective To determine the incidence and risk factors for ROPin premature infants.Methods This retrospective study included premature infantsborn in Stella Maris Women's and Children's Hospital and admittedto the neonatal intensive care unit (NICU) and NeonatologyDepartment from November 2009 to May 2012. We included allpremature infants with body weight (BW) < 1500 g or gestationalage (GA) < 32 weeks, and selected infants with BW 1500 - 2000g or GA > 32 weeks with unstable clinical courses who had beenscreened for ROP. Data was analyzed with Fisher's exact test andindependent t test.Results Of the 48 premature infants in the study, ROP wasdetected in 6 (12.5%) of the subjects. Stages ofROPwere classifiedaccording to the International Classification ofRetinopathyof Prematurity. Stage 1 ROP was detected in 1 (2.1 %) subject;stage 2 ROP was detected in 3 (6.25%) subjects; and stage 3ROP was found in 2 ( 4.2%) subjects. The 2 infants with stage3 ROP required surgery. No ROP was detected in infants withGA 30 weeks or BW > 1250 g. Respiratory distress syndrome(RDS), sepsis, blood transfusion, and apnea were found to beassociated with development ofROP. Duration of oxygen therapywas found to be a significant risk factor for ROP in a comparisonof the no ROP group to the ROP group: 14.0 (SD 9.508) daysvs. 3.81 (SD 5 .218) days, respectively (P<0.05). In addition,the duration of continuous positive airway pressure (CPAP)usage was also a significant risk factor for ROP, with 1.83 (SD1.329) days in the ROP group vs. 0.76 (SD 1.122) days in theno ROP group (P<0.05).Conclusions The incidence of ROP in the premature infants inour study is 12.5%. Retinopathy of prematurity is associated withlower BW, lower GA, lower Apgar score at the 5th minute, RDS, sepsis, apnea, blood transfusion, aminophylline usage, as well aslonger duration of oxygen therapy and CPAP usages.